PENGAWASAN KINERJA BIROKRASI MELALUI E-KINERJA STUDI KASUS PEMERINTAH KOTA SEMARANG - Wahyu Hanie Pratiwi; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2018)
This research has a goal to to find out the extent to which the success of the Bureaucratic Reform through the application of derivatives of e-government derived into an online-based system application, e-Kinerja in overseeing the running of government in Semarang City through the performance of civil state apparatuses, in which civil servants. How the implementation and implementation of a recent system change is implemented which results can be utilized by the people of Semarang City, as users and recipients of public services. BKD Semarang City as one of the government organization in the field of Personnel which build online system e-Kinerja gradually to SKPD in Semarang City area. BKD Semarang City is able to improve the performance of civil state apparatus through e-Kinerja.The type of research used in this research is analytical descriptive research type through qualitative approach. Sources of data used in the form of primary data derived from the results of in-depth interviews of research informants and secondary data in the form of archives and documentation. The technique of selecting informants using purposive sampling.The results of the study found that the implementation and application of online e-Kinerja system application succeeded to be a tool that plays a role in supervising the performance of bureaucracy in Semarang City. The success of development and implementation and implementation of e-Kinerja in all SKPD is considered very influential on the people of Semarang City. The success of Semarang City BKD's achievement in implementing this e-Kinerja online system also influences the services provided to the people of Semarang City, such as health services, education services, service in the field of personnel.Keywords : Supervision, Bureaucratic Performance, e-Kinerja